Planning and market regulation: Strengths, weaknesses and interactions in the provision of less inequitable and better quality health care - Maureen Mackintosh (The Open University, Economics Department, 2007)
This paper argues that planned health care provision and market regulation play distinct roles in relation to the effective provision of equitable health care. Governmental planned provision has as a core objective ensuring that the health system is redistributive and that the poor have access to competent care. Market regulation has as its central objective the shaping of the role and behaviour of the private sector within the health system. Management of the health system as a whole, which is a governmental responsibility, therefore requires the integration of planning and regulation in a manner appropriate to each particular context.
Keywords: 330; Gesundheitsversorgung; Regulierung; Wirtschaftliche Effizienz; Gesundheitswesen; Welt